Implementación de un sistema de inventario para la gestión en la mercancía de la tienda de regalos Maffra en la ciudad de Duitama - Ruidiaz, Erika (Universidad Antonio Nariño, 2024)
Managing an inventory system and carrying out proper control over it, is what leads organizations to have a correct balance in what is needed and what is not, good inventory management of a company is necessary for strengthening and growth of it's on the market.